A ceramic-hydrogel composite bone scaffold and its preparation method and application
By penetrating temperature-sensitive and photosensitive hydrogels into the ceramic bone stent, the ceramic-hydrogel composite bone stent is solved, and the existing ceramic-based bone stent lacks osteogenicity and osteoinduction characteristics are achieved, effectively promoting bone cell migration and bone repair, and improving the speed and effect of bone repair.
Patent Information
- Application Number
- CN202411343407.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-25
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2044-09-25
AI Technical Summary
The existing ceramic matrix composite gradient bone stent lacks osteogenic or osteoinductive properties, which makes it difficult for bone cells to grow into the bone stent, and is prone to inflammation and bone bonding failure in the case of large bone defects.
By infiltrating the temperature-sensitive hydrogel and the photosensitive hydrogel into the ceramic bone scaffold, the ceramic-hydrogel composite bone scaffold is formed, and the stepwise degradation and drug release mechanism of the hydrogel are used to promote bone cell migration and bone repair.
It improves the osteogenic potential and osteoinduction activity of the bone stent, promotes the effective junction of the bone stent with native bone, enhances the speed and effect of bone repair, and inhibits the inflammatory response.
Smart Images

Figure CN119139542B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of composite gradient materials, and in particular relates to a ceramic-hydrogel composite bone scaffold and a preparation method and application thereof. Background Art
[0002] Bone defects are shortages of bone caused by trauma, tumors, and infections. Bone defects larger than 1-2 cm usually cannot be repaired by the body itself. Bone defects larger than the critical size (>1-2 cm) can cause bone nonunion, which not only limits the patient's ability to move, but can also lead to long-term pain, complex disorders, and other complications, seriously affecting the patient's quality of life.
[0003] At present, bone tissue engineering is an innovative and important medical development direction for the treatment of bone defects. Bone tissue material is a natural composite material with multiple gradients and multi-level structures, including organic and inorganic components. The organic component gives the bone elasticity and toughness, while the inorganic component allows the bone to bear high-intensity loads; and the organic and inorganic components of the bone tissue material are mutually permeable, and its macroscopic structure is a gradient structure that gradually transitions from dense cortical bone to spongy cancellous bone. The gradient transition process is accompanied by multiple gradients such as compressive strength, elastic modulus, porosity, tissue composition, and connectivity; in addition, from macro to micro, bone tissue has a complex internal connection network, and a large amount of bone marrow is stored in the millimeter-level pores of cancellous bone. After hematopoiesis, blood vessels distribute nutrients to each bone cell through transverse and longitudinal pores. Adjacent bone cells are connected through micron-level canaliculi. The canaliculi contain tissue fluid, which is responsible for nutrient delivery and waste metabolism between bone cells.
[0004] The invention patent with publication number CN 115042428 A discloses a ceramic-based composite gradient bone scaffold, which has a hierarchical porous structure from foam small pores to mesh macropores (100-1000 μm), which has high porosity while maintaining strong mechanical properties, providing mechanical support during new bone formation. Although the ceramic-based bone scaffold has good biocompatibility and osteoconductivity, it lacks osteogenic or osteoinductive properties. In other words, cells can adhere and proliferate well on the bone scaffold, but it is difficult to recruit stem cells to grow into the bone scaffold. In the case of excessively large bone defects, bone cells only stay near the contact between the scaffold and the host bone, while the inside of the bone scaffold is still in a cavity state. In this case, even a sterilized bone scaffold is easily infected, thereby causing inflammation and bone bond failure.
[0005] Although there is a hydrogel periosteum system constructed by combining ceramic-based bone scaffolds (BTE scaffolds) and hydrogels in the prior art, which aims to enhance the bone regeneration rate and deliver key osteoblasts to the damaged area, thereby effectively promoting the rapid integration between the scaffold and the original bone tissue. However, the current research focus is mainly on using hydrogels to make the outer periosteum layer of BTE scaffolds, while the research on deeply integrating hydrogels into the BTE scaffold structure as a multi-composite drug delivery carrier to achieve orderly distribution and controlled release of multi-layer drugs to inhibit inflammatory response, promote angiogenesis and optimize bone formation is still a blank area. Summary of the invention
[0006] The purpose of the present invention is to provide a ceramic-hydrogel composite bone scaffold and its preparation method and application, so as to overcome the shortcomings of the prior art, play a supporting role in the process of new bone formation, recruit bone-derived stem cells to migrate and infiltrate into the scaffold, ensure the osteogenic potential and osteoinductive activity of the bone scaffold, and enable the bone scaffold to be effectively bonded with the native bone.
[0007] In order to achieve the above object, the technical solution of the present invention is:
[0008] In a first aspect, the present invention provides a ceramic-hydrogel composite bone scaffold, comprising a bone scaffold and a hydrogel filled in the bone scaffold; wherein the bone scaffold contains foam holes and mesh holes, the foam holes are holes formed inside the bone scaffold, and the mesh holes are holes formed between the skeletons of the bone scaffold;
[0009] The hydrogel is a thermosensitive hydrogel and a photosensitive hydrogel; the thermosensitive hydrogel is filled in the foam pores; the photosensitive hydrogel is filled in the mesh pores.
[0010] In some other embodiments, the bone scaffold is a ceramic bone scaffold; the pore size of the foam pores is 1-100 μm; and the pore size of the mesh pores is 300-1000 μm.
[0011] In some other embodiments, the viscosity of the thermosensitive hydrogel loaded with vascular ingrowth and osteogenic drugs is less than 100 mPa·s
[0012] Wherein, the thermosensitive hydrogel is a Pluronic series hydrogel.
[0013] In some other embodiments, the photosensitive hydrogel is methacryloyl gelatin.
[0014] The ceramic scaffold in the present invention is a biomimetic structural gradient with porosity and connectivity. Thermosensitive hydrogel and photosensitive hydrogel are infiltrated into the ceramic bone scaffold with a hierarchical structure to obtain a high-strength and high-activity ceramic-hydrogel composite bone scaffold. In addition, in order to further improve the bone repair effect, drugs with vascular ingrowth and osteogenesis and anti-inflammatory drugs can be added to the thermosensitive hydrogel and photosensitive hydrogel, respectively, so as to overcome the shortcomings of the simple ceramic scaffold in terms of osteogenesis and osteoinduction activity, and the preparation of a functional bone scaffold with a multi-level structure and multiple gradients is conducive to the recruitment of stem cells to grow into the bone scaffold.
[0015] In a second aspect, the present invention provides a method for preparing the ceramic-hydrogel composite bone scaffold according to the first aspect, comprising the following steps:
[0016] (1) mixing the thermosensitive hydrogel with a phosphate buffer solution to form a thermosensitive hydrogel solution;
[0017] (2) immersing the ceramic scaffold in the thermosensitive hydrogel solution of step (1), and subjecting the ceramic scaffold to ultrasonic treatment and cross-linking reaction to obtain a ceramic scaffold infiltrated with the thermosensitive hydrogel;
[0018] (3) mixing the photosensitive hydrogel with deionized water to swell and form a photosensitive hydrogel solution;
[0019] (4) Immersing the ceramic scaffold infiltrated with the thermosensitive hydrogel in step (2) into the photosensitive hydrogel solution in step (3), stirring, and irradiating with ultraviolet light to obtain a ceramic-hydrogel composite bone scaffold.
[0020] In some other embodiments, in step (1), the concentration of the phosphate buffer solution is 0.01-0.05 M, the pH is 7-7.5, and the mixing temperature is 4-6° C.; the concentration of the thermosensitive hydrogel solution is 20-25 wt.%.
[0021] In some other embodiments, in step (2), the ultrasonic treatment is for 4-6 hours; and the temperature of the cross-linking reaction is 35-40°C.
[0022] In some other embodiments, in step (3), the swelling is first allowed to stand at room temperature for 1-2 hours; then heated to 40-50° C. and mechanically stirred;
[0023] The concentration of the photosensitive hydrogel solution is 10-15 wt.%.
[0024] In some other embodiments, in step (4), the stirring speed is 200-300 rpm; the stirring time is 4-6 hours;
[0025] The ultraviolet irradiation time is 3-5h.
[0026] The present invention uses a thermosensitive hydrogel to penetrate the primary structure of a ceramic scaffold with a hierarchical structure. The ceramic BTE scaffold is placed in a measuring cylinder filled with a mixed solution of a certain range, and then placed in an ultrasonic cleaning machine for ultrasonic oscillation, assisted by stirring to allow the thermosensitive hydrogel solution to fully enter the foam pores.
[0027] The present invention makes full use of the depth advantage of the measuring cylinder. Based on the Pascal principle, the deeper the water level of the ceramic stent is, the greater the pressure on the bubbles in the small holes of the ceramic stent, and the easier it is to be shattered and discharged under ultrasonic oscillation, so that the thermosensitive hydrogel solution with drugs is easier to enter the small holes. Since there is a connecting structure less than 100 μm on the foam holes of the multi-level stent, the thermosensitive hydrogel can enter every inner corner of the ceramic stent along the connecting structure. The ceramic stent infiltrated with the thermosensitive hydrogel solution is then taken out from the measuring cylinder. Since the viscosity of the thermosensitive hydrogel solution is low, the mixed solution in the grid holes flows out, while the solution in the foam holes is difficult to be easily discharged due to the surface tension of the liquid.
[0028] The ceramic stent infiltrated with the thermosensitive hydrogel as described above is then placed in a drying oven, and a cross-linking temperature is set to perform a cross-linking reaction, so that the thermosensitive hydrogel is fixed in the foam pores, and a ceramic stent filled with the thermosensitive hydrogel solution is obtained. In particular, the thermosensitive cross-linking method can effectively utilize heat radiation to conduct heat, so that the thermosensitive hydrogel in the foam pores inside the ceramic stent is thermally cross-linked.
[0029] Photosensitive hydrogel is used to infiltrate the secondary structure of the ceramic scaffold filled with thermosensitive hydrogel. The ceramic scaffold is placed in a culture dish filled with photosensitive hydrogel solution, and the photosensitive hydrogel solution is fully immersed in the secondary pores by mechanical stirring. The photosensitive hydrogel is fixed on the secondary structure of the ceramic scaffold by cross-linking reaction initiated by ultraviolet light, thereby preparing a composite bone scaffold with a multi-level structure and multiple gradients.
[0030] In a third aspect, the present invention provides a use of the ceramic-hydrogel composite bone scaffold described in the first aspect in preparing a bone repair material.
[0031] The ceramic-hydrogel composite bone scaffold of the present invention has a hydrogel in the ceramic scaffold that is gradually degraded during the bone repair process, thereby providing targeted treatment at each stage of bone repair and improving the bone repair speed. In addition, when drugs with vascular ingrowth and osteogenesis properties and anti-inflammatory drugs are added to the thermosensitive hydrogel and the photosensitive hydrogel, respectively, in the prepared ceramic-hydrogel composite bone scaffold, the hydrogel encapsulating the anti-inflammatory drug is first released in the large pores to inhibit the rejection and inflammation problem during the access of bone tissue, and then the hydrogel encapsulating the drug that is easy for vascular ingrowth and bone growth is released in the small pores to accelerate the solution of bone defects. Finally, the main component of the ceramic BTE scaffold, tricalcium phosphate, is released, further accelerating bone growth and bone healing.
[0032] Compared with the prior art, the present invention achieves the following beneficial effects:
[0033] (1) The present invention infiltrates two hydrogel solutions into a ceramic bone scaffold to prepare a ceramic-hydrogel composite bone scaffold, thereby overcoming the deficiencies of a simple ceramic scaffold in terms of osteogenic performance and osteoinductive activity, and facilitating the recruitment of stem cells to grow into the bone scaffold.
[0034] (2) The ceramic bone scaffold used in the present invention has a bionic structural gradient of porosity and connectivity in the radial direction. After the hydrogel penetrates into it, multiple gradients such as water content gradient and cell distribution gradient are formed, which better imitates the bionic gradient of natural bone and plays a multiple role in the bone repair process.
[0035] (3) The present invention performs graded penetration according to the pores of different scale structures of the ceramic bone scaffold. During the bone repair process, the hydrogel in the ceramic scaffold will be degraded step by step. After the hydrogel is loaded with drugs, the drugs carried by the hydrogel will be released step by step as the hydrogel degradation process occurs, thereby providing targeted treatment at each stage of bone repair and improving the speed of bone repair. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Figure 1 Schematic diagram of the preparation of the ceramic-hydrogel composite bone scaffold in Example 1 of the present invention;
[0037] Figure 2 This is a SEM image of the ceramic bone scaffold used in Example 1 of the present invention;
[0038] Figure 3 Schematic diagram of different infiltration methods used in Example 3 of the present invention;
[0039] Among them: 1. Small holes inside the bone scaffold, 2. Large holes outside the bone scaffold.
[0040] In order to show the positions of various parts, the distances or sizes between them are exaggerated in the figure, and the schematic diagram is for reference only. DETAILED DESCRIPTION
[0041] As described in the background technology, the prior art has the problem that the printed hydrogel bone scaffold does not consider the multi-level layered drug compounding. In order to solve the above technical problems, the present invention proposes a ceramic-hydrogel composite bone scaffold and a preparation method and application thereof. In order to enable those skilled in the art to more clearly understand the technical solution of the present invention, the technical solution of the present invention is described in detail below in combination with specific embodiments and comparative examples.
[0042] Example 1
[0043] A method for preparing a ceramic-hydrogel composite bone scaffold comprises the following steps:
[0044] (1) Preparation of thermosensitive hydrogel solution
[0045] The thermosensitive hydrogel Pluronic F127 was added to 0.01 M phosphate buffered saline (pH = 7.4, 4°C) and stirred. After incubation at 4°C overnight, the gel was completely dissolved and a Pluronic F127 solution with a final concentration of 25% was formed;
[0046] (2) Penetration of the primary structure of the ceramic scaffold
[0047] Immerse the 3D printed ceramic scaffold in a 100 mL measuring cylinder filled with the Pluronic F127 hydrogel in step (1), and then place it in an ultrasonic cleaner for 4 hours of ultrasonic oscillation, with the aid of stirring to allow the Pluronic F127 solution to fully enter the foam pores. Then take out the ceramic scaffold soaked in the Pluronic F127 solution from the measuring cylinder and place it in a drying oven, set the cross-linking temperature to 37°C to perform the cross-linking reaction of the hydrogel, and fix the hydrogel in the foam pores to obtain a ceramic scaffold filled with Pluronic F127 hydrogel;
[0048] (3) Preparation of photosensitive hydrogel solution
[0049] Add the photosensitive hydrogel methacryloyl gelatin into deionized water, let it stand at room temperature for more than 1 hour to swell, then put it into a heated magnetic stirrer or a constant temperature water bath, control the temperature at 40-50°C, and completely dissolve the hydrogel in water by mechanical stirring until the solution becomes clear and transparent. The final photosensitive hydrogel concentration is 10%;
[0050] (4) Penetration of the secondary structure of the ceramic scaffold
[0051] The ceramic scaffold filled with Pluronic F127 hydrogel in step (2) is immersed in the methacryloyl gelatin solution in step (3), placed on a magnetic stirrer, set the speed to 200 rpm, and stirred for 4 hours to allow the methacryloyl gelatin solution to fully penetrate into the mesh pores of the ceramic bone scaffold; then, ultraviolet light is used to induce the cross-linking reaction of the photosensitive hydrogel, and the photosensitive hydrogel is fixed on the ceramic scaffold, thereby preparing a ceramic-hydrogel composite bone scaffold with a multi-level structure and multiple gradients.
[0052] The ceramic bone scaffold is prepared by a direct foam writing method, and the preparation method refers to the paper Guo Weiwei, Junyuan Sun, Jiang Zhaoliang, et al. Hierarchically porous bonescaffold fabricated via direct foam writing with TCP / ZrO2 composite ink[J]. Journal of Alloys and Compounds, 2024: 175513, or the patent with publication number CN 115042428 A, thereby preparing a ceramic bone scaffold with foam pores ranging from 1 to 100 μm and mesh pores ranging from 300 to 1000 μm.
[0053] The properties of the prepared functionally gradient ceramic-hydrogel composite bone scaffold are shown in Table 1.
[0054] Table 1 Properties of prepared ceramic-hydrogel composite bone scaffolds
[0055]
[0056] It can be seen from Table 1 that in the direction parallel to the porosity gradient, the weaker porous structure and hydrogel fail first, so the compressive strength is low, while in the direction perpendicular to the gradient, the stronger ceramic scaffold plays a bearing role, so the compressive strength is high.
[0057] Figure 1 The figure is a schematic diagram of the preparation of a ceramic-hydrogel composite bone scaffold, which includes a bone scaffold and a hydrogel filled in the pores of the bone scaffold. The ceramic scaffold in the present invention is a bionic structure gradient with porosity and connectivity. The ceramic-hydrogel composite bone scaffold prepared by infiltrating a thermosensitive hydrogel and a photosensitive hydrogel into a ceramic bone scaffold with a hierarchical structure has a multiple gradient structure to replace natural bone.
[0058] Figure 2 SEM image of the ceramic bone scaffold used. Figure 2 It can be seen that the 3D printed ceramic bone scaffold has a hierarchical structure; the hierarchical structure has a primary structure composed of foam pores with a pore size of 1-100μm and a secondary structure composed of mesh pores with a pore size of 300-1000μm. According to the pores of different scales of the ceramic bone scaffold, graded penetration is carried out. During the bone repair process, the hydrogel in the ceramic scaffold will be degraded step by step, so as to carry out targeted treatment at each stage of bone repair and improve the speed of bone repair.
[0059] Example 2
[0060] Different from Example 1, the material used for the ceramic bone scaffold is tricalcium phosphate-based composite ceramic;
[0061] The drug added to the Pluronic F127 precursor solution in step (1) to promote bone growth and blood vessel ingrowth is transforming growth factor;
[0062] The anti-inflammatory drug added to the methacryloyl gelatin precursor solution in step (3) is ciprofloxacin.
[0063] The other preparation steps are exactly the same as those in Example 1.
[0064] Figure 3 Schematic diagram of different penetration methods used. The first-level penetration is to stir and dissolve the thermosensitive hydrogel and phosphate buffered saline solution to form a thermosensitive hydrogel precursor solution, add drugs with vascular ingrowth and osteogenesis properties to the thermosensitive hydrogel precursor solution, let it stand overnight, and obtain the thermosensitive hydrogel loaded with vascular ingrowth and osteogenesis drugs; immerse the ceramic scaffold in the thermosensitive hydrogel loaded with vascular ingrowth and osteogenesis drugs, and obtain the ceramic scaffold infiltrated with the thermosensitive hydrogel loaded with vascular ingrowth and osteogenesis drugs through ultrasonic treatment and cross-linking reaction.
[0065] Secondary infiltration is to mix and swell the photosensitive hydrogel with deionized water to form a photosensitive hydrogel precursor solution, add anti-inflammatory drugs into the photosensitive hydrogel precursor solution to obtain photosensitive hydrogel loaded with anti-inflammatory drugs; immerse the ceramic scaffold infiltrated with thermosensitive hydrogel loaded with blood vessel growth and osteogenic drugs into the photosensitive hydrogel loaded with anti-inflammatory drugs, stir and irradiate with ultraviolet light to obtain a ceramic-hydrogel composite bone scaffold.
[0066] After being implanted in the body, the ceramic-hydrogel composite bone scaffold will first degrade the hydrogel in the reticular macropores in the early stage of rehabilitation, while releasing anti-inflammatory drugs, thereby inhibiting the occurrence of inflammation at the trauma site in the early stage of rehabilitation; after the hydrogel in the macropores is completely degraded, the tissue fluid begins to contact the foam pores in the printed filaments, degrading the hydrogel in the foam pores, while releasing drugs that promote blood vessel growth and induce osteogenesis, thereby promoting the growth of new bone in the middle stage of rehabilitation; in the early and middle stages of rehabilitation, due to the slow degradation rate of the ceramic scaffold, it will play a bearing role at the trauma site throughout the entire process, until the hydrogel with a fast degradation rate is completely degraded, the tricalcium phosphate ceramic begins to degrade, and enters the late stage of rehabilitation, and the new bone completely replaces the implanted ceramic-hydrogel composite bone scaffold.
[0067] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A ceramic-hydrogel composite bone scaffold, characterized in that: It comprises a ceramic bone scaffold and a hydrogel filled in the ceramic bone scaffold; wherein the prepared ceramic bone scaffold contains mesh pores and foam pores, the foam pores are pores formed inside the ceramic bone scaffold, and the mesh pores are pores formed between the skeletons of the ceramic bone scaffold; The hydrogel is a thermosensitive hydrogel and a photosensitive hydrogel; the thermosensitive hydrogel is filled inside the foam pores; the photosensitive hydrogel is filled inside the mesh pores; The pore size of the foam pores is 1-100 μm; the pore size of the mesh pores is 300-1000 μm; The viscosity of the thermosensitive hydrogel is less than 100 mPa·s; The method for preparing the ceramic-hydrogel composite bone scaffold comprises the following steps: (1) mixing the thermosensitive hydrogel with a phosphate buffered aqueous solution to form a thermosensitive hydrogel solution; (2) immersing the ceramic bone scaffold in the thermosensitive hydrogel solution of step (1), and subjecting the ceramic bone scaffold to ultrasonic treatment and cross-linking reaction to obtain a ceramic bone scaffold infiltrated with the thermosensitive hydrogel; (3) mixing the photosensitive hydrogel with deionized water to swell and form a photosensitive hydrogel solution; (4) immersing the ceramic bone scaffold infiltrated with the thermosensitive hydrogel in step (2) into the photosensitive hydrogel solution in step (3), stirring and irradiating with ultraviolet light to obtain a ceramic-hydrogel composite bone scaffold; The thermosensitive hydrogel is a Pluronic series hydrogel; The photosensitive hydrogel is methacryloyl gelatin.
2. The ceramic-hydrogel composite bone scaffold according to claim 1, characterized in that: The thermosensitive hydrogel contains drugs with blood vessel growth and bone formation properties.
3. The ceramic-hydrogel composite bone scaffold according to claim 1, characterized in that: The photosensitive hydrogel contains anti-inflammatory drugs.
4. A method for preparing the ceramic-hydrogel composite bone scaffold according to any one of claims 1 to 3, characterized in that: The following steps are involved: (1) mixing the thermosensitive hydrogel with a phosphate buffered aqueous solution to form a thermosensitive hydrogel solution; (2) immersing the ceramic bone scaffold in the thermosensitive hydrogel solution of step (1), and subjecting the ceramic bone scaffold to ultrasonic treatment and cross-linking reaction to obtain a ceramic bone scaffold infiltrated with the thermosensitive hydrogel; (3) mixing the photosensitive hydrogel with deionized water to swell and form a photosensitive hydrogel solution; (4) Immersing the ceramic bone scaffold infiltrated with the thermosensitive hydrogel in step (2) into the photosensitive hydrogel solution in step (3), stirring, and irradiating with ultraviolet light to obtain a ceramic-hydrogel composite bone scaffold.
5. The method for preparing the ceramic-hydrogel composite bone scaffold according to claim 4, characterized in that: In step (1), the concentration of the phosphate buffer solution is 0.01-0.05 M, the pH is 7-7.5, and the mixing temperature is 4-6°C; the concentration of the thermosensitive hydrogel solution is 20-25wt.%.
6. The method for preparing the ceramic-hydrogel composite bone scaffold according to claim 4, characterized in that: In step (2), the ultrasonic treatment is performed for 4-6 h; and the temperature of the cross-linking reaction is 35-40°C.
7. The method for preparing the ceramic-hydrogel composite bone scaffold according to claim 4, characterized in that: In step (3), the swelling is first allowed to stand at room temperature for 1-2 hours; then the temperature is raised to 40-50°C and mechanically stirred; The concentration of the photosensitive hydrogel solution is 10-15 wt.%.
8. The method for preparing the ceramic-hydrogel composite bone scaffold according to claim 4, characterized in that: In step (4), the stirring speed is 200-300 rpm; the stirring time is 4-6 h; The ultraviolet irradiation time is 3-5h.
9. Use of the ceramic-hydrogel composite bone scaffold according to any one of claims 1 to 3 in the preparation of bone repair materials.
Citation Information
Patent Citations
Additive manufacturing method for constructing multiple continuous gradient functional bone scaffold
CN115042428A
Tissue engineering bone cartilage composite bracket and integrated photocuringable forming method thereof
CN102430151A
Preparation method of 3D printing bio-ink material with controllable material distribution and preparation method of three-dimensional bionic hydrogel scaffold
CN114470328A